Showtime : Magic, Kareem, Riley, and the Los Angeles Lakers dynasty of the 1980s - Pearlman, Jeff (Gotham Books, 2014)
"In Showtime, former Sports Illustrated senior writer Jeff Pearlman presents the complete, no-holds-barred story of the remarkable individuals who cam together to form pro basketball's most legendary dynasty: Johnson, the revolutionary 6-foot-9 point guard who charmed an entire nation with his megawatt smile and incomparable basketball wizardry; Kareem Abdul-Jabbar, the stoppable skyhooking center; and head coach Pat Riley, whose GQ-worthy style and perfectly coiffed hair reflected his basketball genius."--Back cover.